Hey!
---------------------------------------------------------
Question #1:
= 6n^2 - 2n - 3 + 5n^2 - 9n - 6
= 6n^2 + (-2n) + (-3) + 5n^2 + (-9n) + (-6)
= (6n^2 + 5n^2) + (-2n + -9n) + (-3 + -6)
= (11n^2) + (-11n) + (-9)
Answer: 11n² + (-11n) + (-9)
---------------------------------------------------------
Question #2:
= 8c^2 - c + 3 + 2c^2 - c + 2
= 8c^2 + (-c) + 3 + 2c^2 + (-c) + 2
= (8c^2 + 2c^2) + (-c + -c) + (3 + 2)
= (10c^2) + (-2c) + (5)
Answer: 10c² + (-2c) + 5
---------------------------------------------------------
Hope This Helped! Good Luck!